Genetic Relationships Among Portuguese Cultivated and Wild Vitis vinifera L. Germplasm - Cunha, Jorge; Ibáñez, Javier; Teixeira-Santos, Margarida; Brazão, João; Fevereiro, Pedro; Martínez-Zapater, José M.; Eiras‐Dias, José E. (Frontiers in Plant Science, 2020)
The domesticated grapevine spread along the Mediterranean basin from the primary Near East domestication area, where the greatest genetic diversity is found in its ancestor, the wild vine populations. Portuguese wild populations are on the southwestern fringe of the distribution of the Vitis vinifera L. ssp. sylvestris (C.C. Gmel.) Hegi in Europe. During the last Glacial Period they became isolated from the previous continuum that had been the territory of wild vine populations. Archaeological remains of domesticated vinifera grapevines in Portugal date back from 795 Before Common Era (BCE) in the lower Tagus river basin. In this work, 258 Portuguese vinifera varieties and sylvestris plants were characterized using 261 single nucleotide polymorphism (SNP) markers. The study of the genetic diversity of this local germplasm, its population structure and kinship, all framed in their historical and geographical backgrounds, revealed a complex network of first-degree relationships, where only Iberian varieties are involved. Some Iberian genotypes, like Alfrocheiro (Bruñal, in Spain), Sarigo (Cayetana Blanca), Mourisco Branco (Hebén), Amaral (Caiño Bravo), and Marufo (Moravia Dulce) are ancestors of a considerable fraction of all the autochthonous analyzed varieties. A part of the diversity developed was mostly local in some cases as shown by the closeness of several varieties (Vinhos Verdes) to the wild cluster in different analyses. Besides, several evidences of introgression of domesticated germplasm into wild vines was found, substantiating the high risk of genetic contamination of the sylvestris subspecies. All these findings together to the known matching between the wild maternal lineage of the Iberian Peninsula and an important number of Portuguese grapevine varieties (chlorotype A), point out that some of these varieties derive, directly or indirectly, from originally local wild populations, supporting the possible occurrence of secondary events of local domestication, or, at least, of an introgression process of wild into cultivated grapevines.